Kajian Nilai B-Value untuk Menganalisis Aktivitas Seismik di Wilayah Pulau Jawa, Bali dan Nusa Tenggara Barat - Munir, Rahmiati; Nurahmah, Laila; Friesky, Vindhiyah; Imran, Muh; Haryono, Arif (GEOSAINS KUTAI BASIN, 2024)
This study aims to analyze seismic activity in East Java, Bali, and West Nusa Tenggara (NTB) using the b-value parameter. Earthquake data from the USGS catalog (2000–2023) were analyzed using Zmap software. To facilitate the analysis of the spatial distribution of b-values and seismic activity patterns in the study area, the region was divided into three areas: Region 1 covers most of West Java and Central Java, Region 2 includes the southern part of Central Java and part of East Java, while Region 3 covers East Java, Bali, and West Nusa Tenggara (NTB). The analysis steps include separating the main earthquake data, determining the b-value, and spatial mapping. The results show that b-values range from 0.4 to 1.9, where lower values (0.4–1.13) reflect high stress accumulation that may lead to large earthquakes, such as in Lombok, NTB. Conversely, higher values (1.13–1.9) indicate low stress, as seen in Sumbawa and the Indian Ocean. This study concludes that the study area exhibits different seismic activity patterns, with NTB as a high-risk area compared to East Java and Bali, in line with the distribution of b-values.